2020
DOI: 10.1038/s41598-020-74365-6
|View full text |Cite
|
Sign up to set email alerts
|

Dog ownership and adults’ objectively-assessed sedentary behaviour and physical activity

Abstract: Evidence suggests a positive effect of dog ownership on physical activity. However, most previous studies used self-reported physical activity measures. Additionally, it is unknown whether owning a dog is associated with adults’ sedentary behaviour, an emerging health risk factor. In this study, physical activity and sedentary behaviour were objectively collected between 2013 and 2015 from 693 residents (aged 40–64 years) living in Japan using accelerometer devices. Multivariable linear regression models were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
1
18
0
1
Order By: Relevance
“…To our knowledge, there has been no previous study of the association between DO and LPA in older adults. However, our findings extend those from a study on DO and accelerometer-measured physical activity in Japanese middle-aged individuals, showing a similar estimate [ 20 ]. Emerging evidence suggest that LPA may potentially have implications for health in older adults.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…To our knowledge, there has been no previous study of the association between DO and LPA in older adults. However, our findings extend those from a study on DO and accelerometer-measured physical activity in Japanese middle-aged individuals, showing a similar estimate [ 20 ]. Emerging evidence suggest that LPA may potentially have implications for health in older adults.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, we also found that dog owners accumulated 11 more minutes/d of MVPA. In a previous study from Japan, DO was associated with about 7 more minutes/d of accelerometer-measured MVPA in middle-aged adults [ 20 ]. However, that estimate was not statistically significant, perhaps in part due to the smaller study sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence has shown the positive health-related outcomes of having a dog as a companion (Barcelos et al, 2020;Koohsari et al, 2020b;Mubanga et al, 2017;Westgarth et al, 2019). Notably, several studies have highlighted dog walking as a key pathway through which dog ownership may support health.…”
Section: Introductionmentioning
confidence: 99%
“…A adaptação do Censo 2010 também foi utilizada para traçar o perfil domiciliar dos participantes, contemplando questões relativas à localização, tipo e característica do domicílio, bem como renda familiar e existência de outros modos de transporte para uso dos moradores. A próxima categoria é relativa à posse de animais de estimação e foi motivada por evidências que sugerem a redução do sedentarismo em proprietários de cachorros (KOOHSARI et al, 2020). Contempla questões sobre a posse, o hábito de passear com o animal e o tempo de duração do passeio.…”
Section: Metodologiaunclassified